The Mediating Effect of Coping Strategies Between Psychological Capital and Small Tourism Organization Resilience: Insights From the COVID-19 Pandemic, Malaysia - Jalil, Muhammad Farhan; Ali, Azlan; Ahmed, Zeeshan; Kamarulzaman, Rashidah (Frontiers in Psychology, 2021)
Amid difficulty, the psychological capital of small tourism firm owners/managers has been given less attention. In the coronavirus disease-2019 (COVID-19) pandemic, this research examined how psychological capital (self-efficacy, hope, optimism, and resilience) affects organizational resilience. By structural equation modeling (AMOS 21.0), 644 small tourism firm owners in Malaysia were randomly selected to investigate the relationship between psychological capital and organizational resilience, and the mediating effect of problem-focused and emotion-focused coping strategies on this relationship. The findings of the study supported hypothesized relationships, as the psychological capital of small tourism firm owners in Malaysia significantly affects organizational resilience. Furthermore, the study discovered that problem-focused and emotion-focused coping strategies have partial mediating effects on the association between psychological capital and organizational resilience. In the context of small tourism businesses sector, the findings of the study have implications, as the firms identify the recovery procedure in the COVID-19 pandemic.